Parental Divorce and Disordered Eating: An Investigation of a Gene-Environment Interaction - Suisman, Jessica Lynn (2010)
OBJECTIVE: We investigated gene-environment interactions (G×E) for associations between parental divorce and disordered eating (DE). METHOD: Participants were 1,810 female twins from the Michigan State University Twin Registry and the Minnesota Twin Family Study. The Minnesota Eating Behaviors Survey was used to assess DE. We tested for G×E by comparing the heritability of DE in twins from divorced versus intact families. It was hypothesized that divorce would moderate the heritability of DE, in that heritability would be higher in twins from divorced than twins from intact families. RESULTS: As expected, the heritability of body dissatisfaction was significantly higher in twins from divorced than intact families. However, genetic influences were equal in twins from divorced and intact families for all other forms of DE. DISCUSSION: Although divorce did not moderate heritability of most DE symptoms, future research should replicate G×Es for body dissatisfaction and identify factors underlying this unique relationship.